2021
DOI: 10.1002/dac.4911
|View full text |Cite
|
Sign up to set email alerts
|

Ring signature and improved multi‐transaction mode consortium blockchain‐based private information retrieval for privacy‐preserving smart parking system

Abstract: Summary In big cities, the drivers face a major problem in identifying an optimal vacant parking space for their vehicles as the number of vehicles has rapidly grown over the recent years. This objective of determining the available parking space results in wastage of time, air pollution, and traffic congestion. Smart parking systems facilitate the driver to book parking slots and attain real‐time parking information. However, the existing smart parking solutions necessitate the disclosure of sensitive informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Much existing research has proven that blockchain transactions can be linked to retrieve the user's information. For example, in smart healthcare systems [80], this type of attack can track patients' and hospitals' identities, as well as users' locations [81], [82].…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…Much existing research has proven that blockchain transactions can be linked to retrieve the user's information. For example, in smart healthcare systems [80], this type of attack can track patients' and hospitals' identities, as well as users' locations [81], [82].…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…Anonymization (31 papers) [34]- [64] Obfuscation (15 papers) [64]- [78] Multi-tier ML (5 papers) [79]- [83] Decentralized ML (10 papers) [78], [84]- [92] Cryptography (154 papers) [48], [51], [59], [62], [63], [76], [83], [85], [86], [92]- [236] Dataflow (51 papers) [61], [82], [83], [89], [101], [165], [216], [221], [223], [237]- [278] Data summarization (6 papers) [279]- [284] Personal data stores (2 papers) [285], [286] ensure privacy (a) blockchain which is used for verifiability and accountability of data collection, storage and access in IoT environments [31]; and (b) privacybased programming languages, which require information flows and privileges to be declared beforehand, so all the data elements are attached to respective policies [32]. 7) Data summarization: it is a process of creating a concise, yet informative, version of data to preserve the privacy of the original data.…”
Section: Privacy-preservation Technique Primary Studiesmentioning
confidence: 99%
“…Here, the amount of information exchange was carried out to the packet size (in bytes) and the transaction per second. The proposed IACB-HCUPPIR is compared against the RSIMBPIR [24], ECCBPS [21], and PARK CHAIN [18] for the block nodes from 15 increases by 5 to 45. The number of bytes utilized for the proposed and other models is depicted in Fig.…”
Section: Comparative Analysis Of Communication Overheadmentioning
confidence: 99%
“…The results of IACB-HCUPPIR confirmed better results in terms of minimized computation and communication overload with maximized drivers' privacy preservation. As one of the limitations of performance measures of blockchain is the transaction throughput and confirmation latency which was measured for the proposed model against the RSIMBPIR [24], ECCBPS [21], and PARKCHAIN [18] and found that the proposed model obtains better parking slot allocation with less time. One of the limitations of homomorphic encryption requires modification in the client-server application to make it functional, which may increase the cost for practical implementation.…”
Section: Throughput =mentioning
confidence: 99%